Analisis Penggunaan Software PlantNet Terhadap Pemerolehan Konsep Dan Keterampilan Prosedural Siswa - Kiki Septaria; Atika Fatharani (Indonesian Journal of Educational Science (IJES), 2022)
The purpose of this research is to assess the intensity of usefulness of technology in the form of PlantNet software on the idea and process (procedural) abilities of students in the topic of variety of living things after three practical activities. This study employed a pre-experimental design with a control and experimental group of 32 students each. This study focuses on the aspects of the idea and process/procedural responses provided by students after attending th(Prastyo et al., 2021)e practicum with and without the PlantNet software. The findings of the SPSS software study utilizing the unpaired t test (2-tailed) generated by the PlantNet program were able to substantially increase students' conceptual skills (sig. 0.0124 < 0,05) and process/procedural abilities (nilai sig. 0.02523 < 0,05). Further study is intended to examine motivation and gender relatedness to mastery of technologies employed during practicum.